Features of the level of matrix metalloproteinase-2, -3, -9 and tissue inhibitors of metalloproteinases-1, -2, -3, -4 in the aqueous humor of patients with primary open-angle glaucoma - V. V. Chernykh; V. I. Konenkov; O. V. Ermakova; N. B. Orlov; A. N. Trunov (Бюллетень сибирской медицины)
Aim. To study the content of matrix metalloproteinase (MMP)-2, -3, -9 and tissue inhibitors of metalloproteinases (TIMPs) -1, -2, -3, -4 in the aqueous humor of patients with moderate primary open-angle glaucoma (POAG).Materials and methods. The experimental group included 47 patients with verified moderate primary open-angle glaucoma. The control group consisted of 26 patients with uncomplicated cataract. The levels of MMP-2, -3, -9 were determined with Luminex Performance Human MMP Magnetic Panel 3-plex kit (R&D Systems, USA), the concentration of TIMPs-1, -2, -3, - 4 was determined with the Human TIMP Magnetic Luminex Performance Assay 4-plex kit (R&D Systems, USA). The study was carried out using flow-through field fluorometry on a Bio-Plex 200 double-beam laser analyzer (Bio-Rad, USA).Results. The study showed a statistically significant increase in the levels of matrix metalloproteinase-2 and tissue inhibitors of matrix metalloproteinases-1, -2, -3, -4 in the aqueous humor of patients with moderate POAG compared with patients with uncomplicated cataract.Conclusion. The obtained data on high concentrations and imbalance in the levels of matrix metalloproteinases and their tissue inhibitors in the aqueous humor of patients with moderate POAG confirm the role of local inflammation, as well as impairments in the structure of the extracellular matrix and its remodeling in the mechanisms of development of this pathology.